Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.5713/ajas.17.0901
|View full text |Cite
|
Sign up to set email alerts
|

Effects of diet and roughage quality, and period of the day on diurnal feeding behaviour patterns of sheep and goats under subtropical conditions

Abstract: Chewing time, number of eating and ruminating session, and duration of eating bouts are physiologically controlled in small ruminants, though chewing time requires isometric scaling during modelling of intake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 34 publications
1
6
0
2
Order By: Relevance
“…In the same way, [56] and [57] reported that Mg, which cannot be stored in the body are involved in energy generating reaction in the tissue of sheep, while Calcium and Potassium are involved in metabolism and body electrolytes balance that secure the health status of the animal vis-à-vis feed intakes. This agrees with the ndings of [58] and [59] who both reported that mineral supplementation has positive effects on feed preference vis-a vis the feed intake and the DMI. [42] also reported that addition of mineral supplement to the diets of sheep increases the preference of such feed by the animal.…”
Section: Discussionsupporting
confidence: 92%
“…In the same way, [56] and [57] reported that Mg, which cannot be stored in the body are involved in energy generating reaction in the tissue of sheep, while Calcium and Potassium are involved in metabolism and body electrolytes balance that secure the health status of the animal vis-à-vis feed intakes. This agrees with the ndings of [58] and [59] who both reported that mineral supplementation has positive effects on feed preference vis-a vis the feed intake and the DMI. [42] also reported that addition of mineral supplement to the diets of sheep increases the preference of such feed by the animal.…”
Section: Discussionsupporting
confidence: 92%
“…It has been reported that feed intake of lambs is reduced at night as a result of an instinctive fear of predation [ 30 ], so it would result in less excretion of faeces early in the morning. On the other hand, according to Sampaio et al [ 13 ], feed degradation and transit in the rumen are continuous but influenced by actual feed intake.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, in the growing period, P apparent digestibility was greater early in the morning (8:00 a.m.) while in the finishing period, this difference did not persist. As stated earlier, faecal P may include much of the P secreted by saliva that is not reabsorbed [ 35 ], and early morning faecal samples may reflect an increase in undigested P that would be linked to increased salivary P turnover, which is induced by rumination that is usually carried out at night [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that both species shared similar diurnal activity patterns as they share the same cues for grazing and rest, triggered by diurnal light fluctuations including dusk and dawn [24]. Shared activity patterns are common in flocking species, such as sheep, due to nutritional requirements after bouts of rest and in response to social facilitation where initiation or increase in a particular behaviour, such as grazing, can be prompted by increases in the same behaviour by other flock mates [12,[26][27][28][29]. Sharing the same activity patterns over the day as sheep could be seen as beneficial in relation to guarding as they are active at the same time as the flock and exhibit corresponding movement levels in their environments at the same time.…”
Section: Diurnal Activity Patternsmentioning
confidence: 99%
“…In comparison, grazing at night, with accompanying lower levels of vigilance, may heighten the risk of predation and likely provides an advantage to nocturnal predator species such as foxes [46]. This preference for grazing during the day is seen in ruminants, such as sheep, that spent more time standing at night compared to the day enabling increases in levels of vigilance over the nocturnal hours [29]. Exhibiting this behaviour could aid the alpacas in their guardian role, allowing them to increase vigilant behaviours during the nocturnal hours where predation risk is higher.…”
Section: Daily Alpaca Behavioursmentioning
confidence: 99%